0.30(18)+0.05x=0.10(12+x)

Simple and best practice solution for 0.30(18)+0.05x=0.10(12+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.30(18)+0.05x=0.10(12+x) equation:


Simplifying
0.30(18) + 0.05x = 0.10(12 + x)

Multiply 0.30 * 18
5.4 + 0.05x = 0.10(12 + x)
5.4 + 0.05x = (12 * 0.10 + x * 0.10)
5.4 + 0.05x = (1.2 + 0.10x)

Solving
5.4 + 0.05x = 1.2 + 0.10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.10x' to each side of the equation.
5.4 + 0.05x + -0.10x = 1.2 + 0.10x + -0.10x

Combine like terms: 0.05x + -0.10x = -0.05x
5.4 + -0.05x = 1.2 + 0.10x + -0.10x

Combine like terms: 0.10x + -0.10x = 0.00
5.4 + -0.05x = 1.2 + 0.00
5.4 + -0.05x = 1.2

Add '-5.4' to each side of the equation.
5.4 + -5.4 + -0.05x = 1.2 + -5.4

Combine like terms: 5.4 + -5.4 = 0.0
0.0 + -0.05x = 1.2 + -5.4
-0.05x = 1.2 + -5.4

Combine like terms: 1.2 + -5.4 = -4.2
-0.05x = -4.2

Divide each side by '-0.05'.
x = 84

Simplifying
x = 84

See similar equations:

| 7y-8=7y+9 | | -t^2-6t=0 | | -3v=13 | | 2x+3=66 | | 7/13x=0 | | 4+3(4x-4)=6-4(2x+1) | | -x^2-13x=0 | | 4t-23=-15+2t | | 3+4(5x-4)=6-4(2x+1) | | x*4+2=14 | | x-1/6-1=x-9/7 | | -y^2-7y=0 | | 4x-9=-29+9x | | -32+9y=5 | | b^2-10b=0 | | 3x+6+6=13 | | x^2+8x=14x | | 2r^2+250=0 | | 7+4(5x-4)=8-3(2x+1) | | 3(7j+2)/4=12 | | 3(3x-9)=(x-3) | | 26+17+22+x/4 | | 9z-5c=30+c | | 5+4(5x-4)=7-3(2x+1) | | 5/6x-2/11x | | -a^2+11a=0 | | 5/6X+6/7-2/11X | | 2x+10+4(-x)=(-x)+(-20) | | 10d+5=7d+32 | | 2/5x+3=9 | | (1.49+0.59+0.49)=30.84+0.30 | | (7x-8)(3x+9)= |

Equations solver categories